45b+6a-3ab-90=x во 2ой -у во 2ой-х-у=60+6ab-3ab-12a=x(y-5)-y(5-y)=(3a во 2ой-A+2)+(-3a во 2ой+3а-1)-(а во 2ой-1)

Ответы:

( 45b — 3ab) + ( 6a — 90) = 3b(15 — a) + 6( a — 15) = — 3b(a -15) + 6(a — 15)== ( a — 15)( 6 — 3b) = 3( 2 — b)(a — 15)x^2 — y^2 — x — y = ( x^2 — y^2) — ( x + y) = ( x — y)(x + y) — ( x + y) == ( x + y)(x — y — 1)60 + 6ab — 3ab — 12a = 60 + 3ab — 12a = 3( 20 + ab — 4a)x( y — 5) + y( y — 5) = ( y — 5)(x + y)( 3a^2 — a + 2) + ( — 3a^2 + 3a — 1) — ( a^2 — 1) = 3a^2-a+2-3a^2+3a-1-a^2+1== — a^2 + 2a + 2

Ответы на похожие вопросы: